Fenomena Pergeseran Budaya Pemberian Hadiah (贈答文化(ぞうとうぶんか)) dalam Tradisi Masyarakat Jepang - Roberto Masami Prabowo (Bina Nusantara University, 2014)
In Japan there is a culture of gift-giving, known as zōtōbunka. This culture is done every year in summer and winter to honor superiors or to maintain relationships between relatives. With the development of times and the incidence of financial crisis in the 1990s, this culture began to be abandoned by the Japanese because of various factors including the economic factors of capitalist society. This study analyzed using descriptive analytical approach with the main data corpus of books, electronic books, websites on the internet, news articles, magazines, and so on. Culture of gift-giving in Japan is explained also with cultural history that originated in China and the trend in Japan today. The conclusion of this paper described the problems in Japan's culture of gift-giving in addition to economic problems, the problem stems from a change or transition from an agrarian society to capitalist society.